A Semikinetic Model of Plasmasphere Refilling Following Geomagnetic Storms and Comparison With Hydrodynamic Results. Issue 7 (23rd July 2020) - Chatterjee, K.; Schunk, R. W.
Abstract: The objective of this paper is the development of a kinetic model for plasmasphere refilling following geomagnetic storms. The kinetic model is based on the "particle‐in‐cell" method, a method based on the simulation of particle motion and thus well suited to high altitude, low‐density regimes, where the plasma transport equations are not valid. The model was validated with exact, analytical benchmarks, which are provided in this paper. The refilling results obtained from the kinetic model were then compared with results from a recently developed hydrodynamic solution methodology based on the "flux‐corrected transport" method, and the limitations of hydrodynamic modeling for low‐density flow at high altitudes were explored. Plain Language Summary: The objective of this paper is the application of recently developed hydrodynamic and kinetic models to the plasmasphere refilling problem following geomagnetic storms. The refilling results for H + ions were compared with a view to understanding the underlying physics. Key Points: Developed a kinetic model for the plasmasphere refilling problem following geomagnetic storms Compared the kinetic results with results from a previously developed hydrodynamic model The limitations of hydrodynamic modeling at high‐altitude, low‐density regimes are explored